Predictive Value of Academic Anxiety for Academic Achievement of University Students - Maliha Nasir، Amir Zaman (PJE, 2023)
Academic anxiety is a well-known concept. Usually when students transit from one institution to another, they have both positive and negative feelings. The uncertainty of a new academic environment may provoke anxious feelings. These feelings may affect student’s academic achievement. This research paper intended to investigate whether or not academic anxiety and academic achievement of university students are related. Also, the predictability of academic anxiety for academic achievement was intended to be measured.Predictive Value of Academic Anxiety for Academic Achievement of University Students